The low temperature epitaxy of Ge on Si (100) substrate using two different precursors of GeH4 and Ge2H6 - Kil, Yeon-Ho; Yuk, Sim-Hoon; Kim, Joung Hee; Kim, Taek Sung; Kim, Yong Tae; Choi, Chel-Jong; Shim, Kyu-Hwan (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
We have investigated the initial stage of low temperature epitaxy (LTE) of Ge on 8 ''-dia. Si (100) substrate using a rapid thermal chemical vapor deposition (RTCVD) with two different precursors of GeH4 and Ge2H6. The quality of LTE Ge films such as surface morphology, defects and crystallinity were analyzed using SEM, AFM and TEM. Experimental results confirmed that the LTE Ge using Ge2H6 precursor was much more beneficial than the LTE using GeH4 in terms of growth rate (x 10), stress relaxation (85% at surface), and crystal quality (low TDDs). The discrepancy looks originated from the weak GeAGe bonds requiring their dissociation energy small compared to the GeAH bonds in GeH4 precursors, and the abundant supply of GeH3 molecules should stimulate chemical reactions at free surface sites. Our LTE technology would be promising for very thin Ge virtual substrate as well as be beneficial for nano-micro electronic devices in need of low temperature processes below 300-500 degrees C. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: THREADING-DISLOCATION DENSITIES; GROWTH; SILICON; LAYER